Pattern Transfer Printing (PTPTM) for c-Si Solar Cell Metallization. (April 2015) - Lossen, J.; Matusovsky, M.; Noy, A.; Maier, Ch.; Bähr, M.
Abstract: Pattern Transfer Printing (PTP TM ) is a patented novel non-contact printing technology developed and commercialized by Utilight for advanced front side metallization of c-Si PV solar cells. As PTP TM is based on laser induced deposition from a polymer substrate, the geometry of the printed features is not restricted by the characteristics of a printing screen, allowing for much finer, higher and uniform fingers. We present the results achieved by printing the front side finger lines and bus bars of mono- and multi-crystalline solar cells with PTP TM technology and compare these with results of neighboring cells manufactured by state-of-the-art screen printing technology. Finger lines with high aspect ratio and uniform line shape down to 20 μm width could be printed. Solar cells with 29 μm wide double printed PTP finger lines show an efficiency increase of up to 0.4%abs .